165k views
4 votes
f(x) = |2x + 3| - 5g(x) = 7Find (f - g)(x).O A. (f - g)(x) = 2x – 21 – 7B. (f - g)(x) = 2x] – 9C. (f – g)(x) = |2x +3| – 12O D. (f - g)(x) = (2x – 9|

User JoCuTo
by
5.6k points

1 Answer

4 votes

Given:

f(x) = |2x + 3| - 5

g(x) = 7

Let's find (f - g)(x)

To find (f - g)(x), subtract function g(x) from function f(x).

We have:

(f - g)(x) = f(x) - g(x)

= [|2x + 3| - 5] - [7]

Subtract 7 from - 5:

|2x + 3| - 5 - 7

= |2x + 3| - 12

Therefore:

(f - g)(x) = |2x + 3| - 12

ANSWER:

(f - g)(x) = |2x + 3| - 12

User Hmir
by
5.7k points